2009
DOI: 10.1007/s00442-009-1277-1
|View full text |Cite
|
Sign up to set email alerts
|

Temperature is the key to altitudinal variation of phenolics in Arnica montana L. cv. ARBO

Abstract: Plants in alpine habitats are exposed to many environmental stresses, in particular temperature and radiation extremes. Recent field experiments on Arnica montana L. cv. ARBO indicated pronounced altitudinal variation in plant phenolics. Ortho-diphenolics increased with altitude compared to other phenolic compounds, resulting in an increase in antioxidative capacity of the tissues involved. Factors causing these variations were investigated by climate chamber (CC) experiments focusing on temperature and ultrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(107 citation statements)
references
References 18 publications
4
100
0
3
Order By: Relevance
“…Similar shifts in the quercetin:kaempferol ratio have been observed in plants grown under temperature stress (Albert et al 2009). Quercetin has a higher quenching capability than kaempferol (Rice-Evans et al 1996), and it was theorized that under temperature stress more quercetin was produced because of this quenching ability (Albert et al 2009). Similar effects may occur in soybeans growing under (Piubelli et al 2005).…”
Section: Discussionmentioning
confidence: 64%
“…Similar shifts in the quercetin:kaempferol ratio have been observed in plants grown under temperature stress (Albert et al 2009). Quercetin has a higher quenching capability than kaempferol (Rice-Evans et al 1996), and it was theorized that under temperature stress more quercetin was produced because of this quenching ability (Albert et al 2009). Similar effects may occur in soybeans growing under (Piubelli et al 2005).…”
Section: Discussionmentioning
confidence: 64%
“…The amounts of flavonoids and caffeic ester derivatives generally increased with these environmental parameters. Especially, the impact of temperature seems to be of importance which is supported by results from climate chamber experiments performed in the group of C. Zidorn (Albert et al, 2009) who identified low temperature as a key factor for the accumulation of phenolic compounds in alpine plants.…”
Section: Total Content Of Flavonoids and Phenolicsmentioning
confidence: 76%
“…18 For Arnica montana for example, temperature is the key factor on the alterations of the phenolic compounds in higher altitudes. 19 Another example is the case of Brassica oleracea, that high levels of UV radiation led to increase the concentration of flavonoids, however the changes induced by UV did not alter the capacity to attract herbivore insects. 20 In the present work, we could not explain exactly the factors that are responsible for the correlation between the caffeoylquinic acids and flavonoids higher concentrations and the rainy season.…”
Section: Discussionmentioning
confidence: 99%